Creative Beauty of Language in Folksongs: Examples from the Maithili Folksongs - Rai, Vishnu S. (Bhashalok भाषालोक, 2026)
Folksongs function as a mirror of a culture. They vividly describe common people's happiness and sorrow, their desires and dreams, every up and downs of their lives. They mesmerize us by their beauties and charms. Sadly, despite the desperate effort of some true folksong-lovers, folksongs are dying a slow death. There is a false belief that folksongs are inferior to poetry and modern songs which are more creative and beautiful. The present paper tries to show how this belief is false. It starts with a brief introduction of folksong, followed by the discussion of what 'creativity' means in relation to poetry and folksong, and presenting plenty of examples of folksongs which show how creative they are in the use of poetic devices and figures of speech. Finally, it ends with a short discussion of the causes of their gradual disappearance. The examples are taken by the Maithili folksongs.